A cross-sectional study of disturbed eating attitudes and behaviours in medical students - ., Panchami; Samuel, Teenu (International Journal of Research in Medical Sciences, 2017)
Background: The final phase of medical school is characterized by many demands, requirements, and responsibilities, in addition to insecurities that typify the end of the program.Weight and shape concerns are also considered part of the core pathology of eating disorders. The purpose of this study is to investigate eating attitudes and to correlate disturbed eating habits with anxiety, self-esteem, body weight satisfaction and BMI in medical students. Methods: This is a cross-sectional observational study in a random sample of medical students aged between 17-21years including a total of 150 medical students. Information was be gathered from a structured questionnaire on eating attitudes and behaviours (eating attitude test -26, EAT-26), anxiety (Beck anxiety inventory), self-esteem (Rosenberg Self-Esteem Scale), fear of being overweight (body image and eating questionnaire for adults-16). Data was represented as mean±S.D. Chi-square test and Pearson’s correlation was used to investigate the relation between different parameters. P value less than 0.05 was found to be significant. Results: In this study, 4.7% of medical students were found to have eating disorder and all were girls. On comparison of eating score with anxiety showed a positive correlation (p=0.001), positive correlation between EAT score and body image dissatisfaction (p=0.001), no significant relationship between self-esteem (p=0.73) and no significant relationship between EAT score and BMI (p=0.294). Conclusions: The prevalence of eating disorder symptoms in this study was calculated using the cut-off scores of the questionnaires, which indicate possible cases of eating disorders. A diagnostic interview is necessary to corroborate the self-report data and to obtain an accurate estimate of prevalence of full syndrome eating disorders.